2007 International Conference on Computational Intelligence and Security (CIS 2007) 2007
DOI: 10.1109/cis.2007.129
|View full text |Cite
|
Sign up to set email alerts
|

An Improved Competitive and Cooperative Learning Approach for Data Clustering

Abstract: The recently proposed Competitive and Cooperative Learning algorithm(CCL) (Cheung 2004) has provided a promising way to perform the data clustering without knowing the number of clusters. Nevertheless, its performance is somewhat sensitive to the initialization of seed points. Also, its cooperative mechanism is applicable to the homogenous clusters only. In this paper, we will therefore suggest using the FSCL algorithm to initialize the seed points such that each cluster of data will at least have a seed poin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2009
2009
2022
2022

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 8 publications
(5 reference statements)
0
3
0
Order By: Relevance
“…(2) What is the perception of teachers and students towards the impact of cooperative learning (CL) methods on students' academic achievement and laboratory proficiency?…”
Section: Research Questionsmentioning
confidence: 99%
See 1 more Smart Citation
“…(2) What is the perception of teachers and students towards the impact of cooperative learning (CL) methods on students' academic achievement and laboratory proficiency?…”
Section: Research Questionsmentioning
confidence: 99%
“…Even though the educationists had made efforts in improving teaching-learning processes, instructional designers are still searching and experimenting to get best methods for optimal academic performance of the students [2]. is is because, in the traditional approach of teaching, most of the class time is spent by teachers talking and students watching and listening, and cooperative learning appears to be discouraged [3].…”
Section: Introductionmentioning
confidence: 99%
“…Despite the effort educationists had made, Indexed African Journals Online: www.ajol.info instructional designers are still searching and experimenting to get better methods for achieving mastery and internalized learning in students. "Best methods for optimal academic performance/achievement are still being sort for" (Wang, Pei, and Cheung, 2007) Felder and Brent (1994) observed that the traditional approach to college teaching, most class time is spent with the teacher talking and students watching and listening. The students work individually on assignment, and co-operation seems to be discouraged.…”
Section: Introductionmentioning
confidence: 99%